A kind of magic : Die Kunst des Verwandelns = The Art of Transforming - Bürgi, Brigitt; Fischer, Peter; Rüttimann, Sylvia; Exhibition. A Kind of magic : Die Kunst des Verwandelns = The Art of Transforming. Kunstmuseum Luzern. 2005-08-06. 2005-11-27 (Luzern : Kunstmuseum Luzern, 2005)
Viola, Bill ; Höller, Carsten ; Searle, Berni ; Banz, Stefan ; Nanxing, Xie ; Smith, Kiki ; Chihuly, Dale ; Müller, Victorine ; Laing, Rosemary ; Stalder, Nicoletta ; Martin, Agnes ; Hersberger, Lori
biog., bibliog. per kunstenaar
Duits
Engels
boek